2019
DOI: 10.1038/s41598-019-52971-3
|View full text |Cite
|
Sign up to set email alerts
|

Isodeoxyelephantopin, a Sesquiterpene Lactone Induces ROS Generation, Suppresses NF-κB Activation, Modulates LncRNA Expression and Exhibit Activities Against Breast Cancer

Abstract: The sesquiterpene lactones, Isodeoxyelephantopin (IDET) and Deoxyelephantopin (DET) are known to exhibit activities against some cancer types. The activities of these lactones against breast cancer and the molecular bases is not known. We examined the efficacy of lactones in breast cancer preclinical model. Although both lactones exhibited drug like properties, IDET was relatively effective in comparison to DET. IDET suppressed the proliferation of both invasive and non-invasive breast cancer cell lines. IDET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…Gemcitabine in combination with p65 siRNA can control the proliferation of pancreatic cancer cells and induce apoptosis as well, both in vivo and in vitro, and curtail the growth and angiogenesis of tumors in nude mice, and this can be a welcome solution as pancreatic cancer treatment is an important issue all over the world [ 44 ]. Recently, studies reported that isodeoxyelephantopin (IDET) may function as an anticarcinogenic via the NF- κ B inactivation and the regulation of oncogenic lncRNA expression in breast cancer [ 45 ]. In addition, NF- κ B may present a unique target for tumor avoidance and therapy in combination with inhibition of transcription factors, such as Stat3 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine in combination with p65 siRNA can control the proliferation of pancreatic cancer cells and induce apoptosis as well, both in vivo and in vitro, and curtail the growth and angiogenesis of tumors in nude mice, and this can be a welcome solution as pancreatic cancer treatment is an important issue all over the world [ 44 ]. Recently, studies reported that isodeoxyelephantopin (IDET) may function as an anticarcinogenic via the NF- κ B inactivation and the regulation of oncogenic lncRNA expression in breast cancer [ 45 ]. In addition, NF- κ B may present a unique target for tumor avoidance and therapy in combination with inhibition of transcription factors, such as Stat3 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical descriptor and drug-like properties of picein (PubChem ID: 92123) and gastrodin (PubChem ID: 115067) were observed by using Lipinski’s rule of 5 ( ), where this rule was specially designated for the selection of small druggable compounds [ 40 , 41 ]. Conical SMILE IDs is a specific and particular chemical structure characteristic of every chemical compound which is usually mentioned in chemical databases.…”
Section: Methodsmentioning
confidence: 99%
“…Elephantopus scaber L., a medicinal plant, is commonly known as “tawmonlar” in Myanmar traditional medicine, “Tutup bumi” in Malaysian, “Elephant’s foot” in English, “Didancao” in traditional Chinese medicines (TCM), and “Gobhi” in Hindi [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Elephantopus genus is widely distributed all over the world, especially in east Asia, southeast Asia, Africa, Australia, India, Europe, and South America [ 16 , 21 , 22 , 23 , 24 , 25 ]. Only Elephantopus scaber, one of the 32 species of genus, is known to grow in India [ 26 , 27 ].…”
Section: Natural Sources and Anti-cancer Activities Of Det And Idetmentioning
confidence: 99%